The effect of communication in changing health-risk behaviors (One Health & Risk Management, 2021)
Introduction. Human behavior plays a central role in the maintenance of health and the prevention of disease. Effective communication is neglected in the local health system but successfully used in countries with a lower disease rate and with an advanced healthy lifestyle. This action can encourage and serve as a model for changing harmful behavior and habits that are not always fully notified by the population.Health communication attempts to persuade the affected group to engage in certain behavior through accessing information. Intervention measures in changing the behaviors in the affected group are an area of concern and must be fully supported by both the government and non-governmental organizations. However, society-wide change is slow.Majority of health communication researchers insist on behavior change programs that aim to increase knowledge, stimulate dialogue, promote attitude change, reduce stigma, and improve skills. Success of communication is determined by a variety of factors that may include: how good is the access of the target group to information, whether the target group has acquired sufficient knowledge and skills to perform the behavior among others.Material and methods. A cross-sectional epidemiological research was carried out by using the descriptive method. The study involved the general population from the Republic of Moldova aged over 18.The research was conducted during March-April, 2020 with the informed online consent from respondents. Participation in this study was absolutely voluntary. The questionnaire included 30 questions. The study involved 1076 people with the age ranged between 26-34 years.Results. Most participants reported that their health depends on nutrition, for about 95.4%, physical activity – 80.4%, routine medical checkup – 47.8% and the avoiding of risk factors (alcohol, smoking) – 35.9%. Also, they tend to quit smoking under the influence of messages on tobacco products – 4.7%. The population is informed about the influence of health risk factors on the Internet and social networks for about 87.7%, through TV programs – 38.9% and by the GPs – 12.2%. 83.5% of the interviewed population mentioned that they are ready to change their behavior when a message is broadcast with positive content. Messages with practical examples could influence the change in health behavior for about 23.4% of respondents. Almost half of the interviewed population (42.3%) believe that the population would change their behavior through health promotion programs, 22.7% of interviewees think that there are changes in population behavior, but only for a short-term, and 21.7% of them answered that the population is rarely determined to change their behavior through health promotion programs.Conclusions. Effective communication for changing health risk behavior in the media has some shortcomings, although the population is motivated to switch some bad habits as a result of broadcasting several programs and messages in health promotion.